Podpora prodeje a reklama konkrétní společnosti - Havránková, Leona (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Bakalářská práce se zaměřuje na problematiku podpory prodeje a reklamy společnosti AD Gastronomie AG, která provozuje irský pub. Práce obsahuje teoretickou část, ze které poté vychází část analytická. Účelem analytické části je představení společnosti a analýza její současné marketingové situace. Výsledky dílčích analýz poté určují, jaká doporučení lze firmě navrhnout. Tato doporučení by po realizaci vedla ke zlepšení podpory prodeje a reklamy společnosti, což by zajistilo oslovení nových zákazníků a udržení zákazníků současných.

The bachelor thesis focuses on the issue of sales promotion and advertising of the company AD Gastronomie AG, which manages an Irish pub. The thesis starts with a theoretical part, providing a knowledge base for the following analytical part. The purpose of the analytical part is the introduction of the company and an analysis of its current marketing situation. The results of the partial analyses will then determine possible recommendations for the company. Implementing those recommendations should lead to the improvement of the sales promotion and advertising, which would result in an inflow of new customers and securing the regular customers.
Sales Promotion and Advertising of Company
Keywords: Reklama; marketingová komunikace; marketingová strategie; podpora prodeje; irský pub; Advertising; marketing communication; marketing strategy; sales promotion; Irish pub